Time-to-recovery after cesarean section delivery among women who gave birth through cesarean section at Hawassa University Comprehensive Specialized Hospital, South Ethiopia: A prospective cohort study. - Anteneh Fikrie; Rahel Zeleke; Henok Bekele; Wongelawit Seyoum; Dejene Hailu; Zelalem Jabessa Wayessa; Girma Tufa; Takala Utura; Male Matie; Gebeyehu Dejene Oda (PLOS Global Public Health)
Cesarean deliveries have become a major public health problem worldwide in recent decades. In addition, information on the quality of service, as measured by timely recovery is scarce. This study was assessed predictors of recovery time after cesarean section among women who delivered by cesarean section at Hawassa University Comprehensive Specialized Hospital (HU-CSH) Southern Ethiopia. Institution-based prospective cohort study design was conducted among 381 study participants from July to August 2020. A consecutive sampling technique employed to select study participants. A pre-tested structured questionnaire was used to collect the data. The data were entered and analyzed by Epi info version 7 and SPSS respectively. Bivariable and multivariable Cox regression used to identify the predictors of time-to-recovery after cesearean section. Adjusted Hazard Ratio (AHR) with the respective 95% confidence intervals (CIs)and p-value <0.5 was used to declare statistical significance. A total of 369 mothers who undergone cesearean section were followed for 1,042 person-days of observation. The timely recovery (within 4 days) was found to be 96.2% [95%CI: 94.04-98.4%] and the overall median (IQR) time of recovery was 2.00 (2, 3) days. The study revaled that the Incidence density rate (IDR) of timely recovery was found to be 0.34 per person-days or 2.38 per person-week. Whereas, the cumulative probability of not recovered on the 1st and 4th day was 0.995 and 0.038 respectively. This study found that women who had ANC follow-up (AHR = 1.49, 95%, CI: 1.05-2.10) and discharge from the wound site (AHR = 0.13, 95%, CI: 0.03-0.56) were identified as a significant positive and negative predictors of time-to-recovery after CS delivery respectively. The rate of early recovery obtained by this study was comparable to the global level figures. Still, the cleanness of the surgical site to prevent the incidence of postsurgical site CS delivery is very essential.